2021
DOI: 10.3390/buildings11040169
|View full text |Cite
|
Sign up to set email alerts
|

Post Occupancy Evaluation of School Refurbishment Projects: Multiple Case Study in the UK

Abstract: Buildings inevitably deteriorate with time. Schools buildings are no exception and require refurbishment at times. Despite the UK Government announcing the £1 billion funding for rebuilding 50 schools over 10 years starting 2010–2021, it is common practice for builders and designers to, upon completion of a building project, move on to the next development without considering how the completed building performs. This research undertakes a post occupancy evaluation (POE) of three schools in the West Midlands, U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 67 publications
1
24
0
Order By: Relevance
“…Pragmatism [106] was adopted in order to analyse practitioner perceptions and values, so as to resolve the phenomena under investigation. This overarching epistemological design was contextualised within a case study strategy [107]-specifically, a successfully secured and delivered negotiated project wherein the main contractor was not responsible for the design. The project consisted of a new-build swimming pool and gym at a private dwelling with a floor area of 125 m 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Pragmatism [106] was adopted in order to analyse practitioner perceptions and values, so as to resolve the phenomena under investigation. This overarching epistemological design was contextualised within a case study strategy [107]-specifically, a successfully secured and delivered negotiated project wherein the main contractor was not responsible for the design. The project consisted of a new-build swimming pool and gym at a private dwelling with a floor area of 125 m 2 .…”
Section: Methodsmentioning
confidence: 99%
“…This research adopts inductive reasoning to study qualitative data, using publications as a unit of analysis, where each publication represents an item within the dataset. This dataset is subsequently analysed using an interpretivist approach and a two-step waterfall process [42][43][44][45]. First, a manual literature review is conducted [42,43] to: (i) establish key definitions; (ii) identify the practicalities of teleworking; and (iii) discuss the links between the construction industry and the habitual realities of teleworking and also explore the practicality of construction teleworking.…”
Section: Methodsmentioning
confidence: 99%
“…Upon commencement, all the meeting participants were informed of the research aim and objectives. In addition to the ethics approval given by the Human Subjects Review Committee of the principal investigator's institution, informed consent was obtained and the participants were given assurances that a strict ethical protocol would be adhered to: specifically, confidentiality and anonymity of participants was assured; and the results of the study would be made available to the participants upon request (Zheng and Lai, 2018;Fisher et al, 2018;Ahmed et al, 2021). Then, the study team showed a relationship diagram of the selected indicators, briefed the participants about the interdependencies and influences between the indicators, and invited them to express their opinions and discuss the information shared with them.…”
Section: Methodsmentioning
confidence: 99%